If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(3p + 2) + -2(5 + -8p) = 3(7 + 2p) Reorder the terms: -3(2 + 3p) + -2(5 + -8p) = 3(7 + 2p) (2 * -3 + 3p * -3) + -2(5 + -8p) = 3(7 + 2p) (-6 + -9p) + -2(5 + -8p) = 3(7 + 2p) -6 + -9p + (5 * -2 + -8p * -2) = 3(7 + 2p) -6 + -9p + (-10 + 16p) = 3(7 + 2p) Reorder the terms: -6 + -10 + -9p + 16p = 3(7 + 2p) Combine like terms: -6 + -10 = -16 -16 + -9p + 16p = 3(7 + 2p) Combine like terms: -9p + 16p = 7p -16 + 7p = 3(7 + 2p) -16 + 7p = (7 * 3 + 2p * 3) -16 + 7p = (21 + 6p) Solving -16 + 7p = 21 + 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. -16 + 7p + -6p = 21 + 6p + -6p Combine like terms: 7p + -6p = 1p -16 + 1p = 21 + 6p + -6p Combine like terms: 6p + -6p = 0 -16 + 1p = 21 + 0 -16 + 1p = 21 Add '16' to each side of the equation. -16 + 16 + 1p = 21 + 16 Combine like terms: -16 + 16 = 0 0 + 1p = 21 + 16 1p = 21 + 16 Combine like terms: 21 + 16 = 37 1p = 37 Divide each side by '1'. p = 37 Simplifying p = 37
| 4x-(-3)(-2)=18 | | 4x-16=3x-1.9 | | 4x(-3)(-2)=18 | | 2(6+x)=32 | | -12h-2(2h-6)=-36 | | 3y^4+6y^3+3y^2=0 | | c-62=812 | | 5xy-10x= | | 9x^4+9x^3y-x^2-xy= | | 7m=147 | | 11-(k+3k)=43 | | 1/3,1/4,1/5,1/6= | | 2y-1/3=x | | 42=5v+2 | | 7x-12=8x+3 | | 15y-18=20 | | -18=r-1 | | 3p-1/2)-(p/2-3/2)4-p/2 | | 42=2x-19 | | 16x^4-8x^2y^2-xy= | | -2=-4+n | | 2t+2=t+16 | | 4x+38=6x+8 | | 2u+15=5u | | -9(2b+4)+(19-8)=0 | | 2x^4+x^3-2x-6= | | x-3x+x-3=0 | | 3(c-10)=60 | | (7b-7)-2(3b+3)=-5 | | 4(6y-9)-5y=-3(2-8y)-18 | | 48=4/v | | w/5=85 |